Orcaella Gray 1866 - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Orcaella Gray, 1866. Cat. Seals Whales Brit. Mus., p. 285. TYPE SPECIES: Orca (Orcaella) brevirostris Gray, 1866. COMMENTS: We follow Fordyce (1989), Heyning (1989a), and Lint et al. (1990) in including Orcaella in the Delphinidae, not in the Monodontidae as was recently proposed (Kasuya, 1973; Barnes et al., 1985). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 354, DOI: 10.5281/zenodo.7352970